“文化大革命”时期下放辽宁省北票乡村“知青”研究 (Study On “Sent-Down Youth” During “Cultural RevoLution” In Rural Area Of Beipiao, Liaoning Province) - Wang, Fuqiu (2019)
At the present, Study on “Sent-down Youth” during “Cultural Revolution” in rural area of Beipiao , Liaoning Province have no way to be found. The research on local educated youth is still very brief with no in-depth study. In the absence of these literature data, the collection, collation and analysis of existing data have become an important feature of this study. This research focuses on the comparative study of multiple evidences, including the records during the “Cultural Revolution”, the evidences of the experiences, as well as the analysis of the data after the “Cultural Revolution” . This study begin by introducing the origin and motivation of research, explains on the research background, reasons for cases selection, literature review, research methods and research purposes. The study describes the process of launching a large-scale movement to the countryside and elaborates a series of happenings that have arisen in the rural area from the year of 1968. From chapter three to chapter five, the management of “Sent-down Youth” , the “Sent-down Youth’s” participation in varieties of political movements and the growth process of “Sent-down Youth” in the countryside are being further described and evaluated. The study covered the management process from the large-scale launched of the Sent-down Youth management system from 1968 until the withdrawal of the management institutions in 1973. This study also explained the fate of the “Sent-down Youth” participated in the class struggle movement under the influences of governmental propaganda before “the Lin Biao incident” . After the “Lin Biao incident”, educated youth began to reflect and recognize on themselves, however they still needs obey the management, and are required to participate in the “Learn from Dazhai in Agricultural ” vi movement. The study concludes with a description of the prominence problems that occurred in the countryside in early year of 1976. With the end of the “Cultural Revolution” , the Chinese Communist Party produced profound reflections and promptly tried to end this “Sent-down Youth” movement. This study focuses on a group of youth with the problems they encountered and theirs fate during the Cultural Revolution era” at a particular location. These reflections were not only due to the “Cultural Revolution” was an era of “absurd years” or “absurd events”, but also because everyone was part of this movement. In addition, it is also a movement that affects the longest period of time and has a massive number of participants. Throughout this movement, it mingled with the struggle for rights, personnel ups and downs, honors and gains and losses, and even personal experience. The in-depth studies of the “Sent-down Youth” movement will greatly enrich people's perception during this period of history. Compared to today’s prosperous living conditions in China, the study of the “Sent-down Youth” movements on the mountain and the countryside will inevitably trigger some pains. The narrow thinking had caused backwardness and tragedies, however in turn this had led to corrective and rebuilding movements. As a result, the movement ended the stage of history. This also proved Deng Xiaoping’s claim that with the lessons of the “Cultural Revolution," we learned that we must reformed and open up, by initiating the retirement system, the pension system, the electoral system and others system, etc., China has evolved to an era of civilization and openness. “With history as a mirror, one can understand the rise and fall of a nation." The aim of the People's Republic of China is to build socialism in the undeveloped environment. Throughout the vii process, mistakes, twists and turns are inevitable, and “Cultural Revolution" has the greatest impact among all. The “Sent-down Youth" that been through the Cultural Revolution, their greatest interest and hobby is politics. When the Sent-down Youth went to the mountain and the countryside, they were eager to learn The Chairman Mao’s way. After “the mountain and the countryside campaign ended", they reflected on the reform and opening up policy. They had a new interpretation of Chairman Mao’s “re-education” and realized through personal experience that Mao Zedong and Deng Xiaoping were both great man and also models for Chinese people’s to respect and follow as they brought historic turn to the Chinese nation in different critical times.